METHOD OF TALAQQI MUSYAFAHAH IN TEACHING AL QURAN WA AL-HIFZ DINI CURRICULUM SABK IN PERAK - Norhisham, Muhamad; Azmil, Hashim; Wahyu Hidayat, Abdullah; Muhammad Akramin, Kamarul Zaman; Fatin Ardani, Zamri (Global Academic Excellence, 2019)
This study was conducted to identify the implementation of Talaqqi Musyafahah on teaching al-Quran in Dini Curriculum at the Perak Government Assisted Religious Schools (SABK), to study the level of achievement in Al Quran reading and the relationship between the implementation of Talaqqi Musyafahah with the achievement of Al Quran reading of SABKs’ students. Research information was obtained through quantitative methods from questionnaires involving 304 form four SABKs’ students in Perak. The collected data was processed using the windows program of SPSS software version 22.0. The results of the study indicate that the implementation of Talaqqi Musyafahah was high (mean=4.15, sp.= 0.65) and the achievement of al Quran reading was high (mean=4.28, sp=0.52). The study also shows that there was a moderate high relationship (r=0.514, p <0.01) between the implementation of Talaqqi Musyafahah with the achievement of the al Quran reading. Overall, the relationship between the implementation of Talaqqi Musyafahah with the achievement level was strong. This proved that Talaqqi Musyafahah is important in teaching and learning of al-Quran. Implications from the study show that the implementation of Talaqqi Musyafahah can enhance the achievement of reading the al Quran among the students.